A light scattering model for total internal reflection microscopy of geometrically anisotropic particles. Issue 10 (7th June 2019) - Doicu, Adrian; Vasilyeva, Alina A.; Efremenko, Dmitry S.; Wirth, Christopher L.; Wriedt, Thomas
ABSTRACT: In this paper, a light scattering model for Total Internal Reflection Microscopy (TIRM) is described. The model handles the scattering by an axisymmetric particle of arbitrary orientation situated in the evanescent field near a plane surface, and the imaging of the scattered light via microscope optics. The scattering problem is solved by using the T -matrix method and the rotation addition theorem for spherical vector wave functions, while the image of the scattered field is computed by using the Debye diffraction integral. The numerical simulations provide evidence of two working regimes for TIRM: the first regime, corresponding to an incident angle less than the critical angle of total internal reflection, provides information on the size and the orientation of the particle, while the second regime, corresponding to an incident angle larger than the critical angle of total internal reflection, is recommended for measuring the distance between the particle and plane surface.